Stable isotope evidence of diet breadth expansion and regional dietary variation among Middle-to-Late Holocene Hunter-Gatherers of Central California. (February 2020) - Bartelink, Eric J.; Beasley, Melanie M.; Eerkens, Jelmer W.; Gardner, Karen S.; Wiberg, Randy S.; Garibay, Ramona
Highlights: Isotopic analysis was conducted on human from CA-CCO-548, a site in Central California. Stable isotope and AMS dates reveal dietary variation during the Middle-to-Late Holocene. Isotopic results reflect the importance of terrestrial C3-resources and freshwater fish. Carbon bioapatite results provide support for resource intensification models. Comparison by sex indicate no significant sex differences in adult diet. Abstract: Previous stable isotope research on Middle-to-Late Holocene (6600 cal BP-present) hunter-gatherers of Central California has documented significant regional variation in human paleodiets between the San Francisco Bay Area and Central Valley. In general, this geographically-patterned dietary variation tracks greater consumption of marine food resources in the Bay Area and greater consumption of freshwater and terrestrial food resources in the Central Valley. Using stable carbon and nitrogen isotope analysis of bone collagen, stable carbon isotopes of bone bioapatite, and a large series of AMS dates (5420-2975 cal BP), we examine human paleodiets in 238 burials from CA-CCO-548 (Marsh Creek), located near the Sacramento-San Joaquin Delta, in Central California. Isotopic results support archaeofaunal and paleobotanical findings regarding the dietary importance of terrestrial C3 -resources (e.g., artiodactyls, small seeds, acorns) and freshwater fish. The results further indicate that marine resources were of minor importance and could have been acquired from brackish areas near the mouth of the San Francisco Bay estuary located 9 km away or through trade. Although carbon and nitrogen isotopes of bone collagen suggest continuity in the sources of dietary protein over time. Carbon isotopes of bone bioapatite demonstrate a significant temporal shift toward greater consumption of C3 plant resources, such as acorns and small seeds, consistent with resource intensification models. The paleodiet of the CA-CCO-548 population is similar to contemporaneous groups located to the south and northwest, but is distinct from groups within the Delta and San Francisco Bay Area.